The science and politics of global climate change: A guide to the debate - Dessler, Andrew Emory (Cambridge University, 2013)
In this primer, Dessler and Parson combine their expertise in atmospheric science and public policy to help scientists, policy makers, and the public sort through the conflicting claims in the climate-change debate. The authors explain how scientific and policy debates work, summarize present scientific knowledge and uncertainty about climate change, and discuss the available policy options. Along the way, they explain why the debate is so confusing.